Comparison of health-related quality of life in children with normal hearing and those with cochlear implant at age of 4-6 years (Journal of Fatima Jinnah Medical University, 2020)
ABSTRACTBackground: Hearing impairment during early life years have profound negative consequences on linguistic output, educational, psychosocial and physical functioning. Auditory perception plays a key role in the development of child. Severely hearing-impaired children receiving cochlear implant (CI) before the age of speech and language acquisition may enjoy their quality of life similar to their normally hearing peers. Considering the beneficial effects of CI on quality of life of hearing-impaired child, it is evident to properly investigate the similarity in life quality of children with CI and their normal hearing mates of same age group.Patients and Method: This comparative cross-sectional study was conducted on parents of 50 children, who were allocated in two equal groups by purposive sampling. The questionnaire was administered by interviewing the parent participants using a validated quality of life questionnaire of Children for Parents and findings were compared with the responses from parents of normal hearing children. Responses from both the groups were analyzed by independent sample t-test.Results: Parents of Cochlear Implanted children rated their children’s Health Related Quality of Life positively. All the sub domains showed the similar results except self-esteem. Findings suggest that normally hearing children had better self-esteem than CI children. No significant difference was found between overall Health Related Quality of Life of Cochlear Implanted children and their normally hearing peers.Conclusion: Overall health related quality of life of children with cochlear implant is similar to that of normal hearing peers of same chronological age.
Keywords: Normal hearing; Hearing loss; Quality of Life; Cochlear Implant